VD_FINDINFO Arrêt / 2010 / 796 vom 2. Juni 2010 - VD Tribunal cantonal (2010)
INFIRMITÉ CONGÉNITALE, PRESTATION D'ASSURANCEAI | 1 LAI, 13 LAI, 69 al. 1bis LAI, 83 LOJV, 3 al. 2 LPGA, 47 al. 1 LPGA, 49 LPGA, 57 LPGA, 60 al. 1 LPGA, 61 let. a LPGA, 61 let. b LPGA, 61 let. g LPGA, 2 LPA-VD, 49 al. 1 LPA-VD, 55 al. 1 LPA-VD, 91 LPA-VD, 93 al. 1 let. a LPA-VD, 94 al. 1 let. a LPA-VD, 99 LPA-VD